Effects of Anti-Integrin Treatment With Vedolizumab on Immune Pathways and Cytokines in Inflammatory Bowel Diseases - Rath, Timo; Billmeier, Ulrike; Ferrazzi, Fulvia; Vieth, Michael; Ekici, Arif; Neurath, Markus F.; Atreya, Raja (Frontiers in Immunology, 2018)
Background and aims: Despite proven clinical efficacy of vedolizumab (VDZ) for inducing and maintaining remission in patients with Crohn’s disease (CD) and ulcerative colitis (UC), subgroups of patients have no therapeutic benefit from anti-α4β7 integrin therapy with VDZ. Within this study, we aimed to identify genetic, cellular and immunological mechanisms that define response and failure to VDZ treatment. Methods: Intestinal RNA Sequencing was performed in UC and CD patients before and at week 14 of VDZ therapy. α4β7 expression on peripheral and mucosal immune cells was assessed by flow cytometry and immunohistochemistry. Cellular modes of VDZ mediated action were analysed ex vivo and in VDZ treated IBD patients. Results: Transcriptome analysis showed an impairment of signaling cascades associated with adhesion, diapedesis and migration of granulocytes and agranulocytes upon VDZ therapy. In non-remitters to VDZ therapy, a tissue destructive and leucocyte mediated inflammatory activity with activation of TNF dependent pathways was present, all of which were inhibited in remitters to VDZ. Clinical remission was associated with a significant reduction of α4β7 expression on Th2 and Th17 polarized mucosal CD4+ T cells at week 14 of VDZ therapy and with significantly higher numbers of α4β7 expressing mucosal cells prior to the initiation of VDZ therapy compared to non-remitters. Conclusions: Intestinal α4β7 expression prior to VDZ therapy might represent a biomarker that predicts therapeutic response to subsequent VDZ treatment. Due to high activation of TNF signaling in VDZ non-remitters, anti-TNF treatment might represent a promising therapeutic strategy in VDZ refractory patients.